Perspectiveson the Recent Currency Crisis Literature - Marion, Nancy; Flood, Robert (Washington, D.C. : International Monetary Fund, 1998)
In the 1990s, currency crises in Europe, Mexico, and Asia have drawn worldwide attention to speculative attacks on government-controlled exchange rates and have prompted researchers to undertake new theoretical and empirical analysis of these events. This paper provides some perspective on this work and relates it to earlier research. It derives the optimal commitment to a fixed exchange rate and proposes a common framework for analyzing currency crises. This framework stresses the important role of speculators and recognizes that the government's commitment to a fixed exchange rate is constrained by other policy goals. The final section finds that some crises may be particularly difficult to predict using currently popular methods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet